2022
DOI: 10.1101/2022.02.08.479633
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pairing-dependent plasticity in a dissected fly brain is input-specific and requires synaptic CaMKII enrichment and nighttime sleep

Abstract: In Drosophila, in vivo functional imaging studies revealed that associative memory formation is coupled to a cascade of neural plasticity events in distinct compartments of the mushroom body (MB). In-depth investigation of the circuit dynamics, however, will require an ex vivo model that faithfully mirrors these events to allow direct manipulations of circuit elements that are inaccessible in the intact fly. The current ex vivo models have been able to reproduce the fundamental plasticity of aversive short-ter… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 111 publications
(193 reference statements)
0
1
0
Order By: Relevance
“…The MBON representations are not formed entirely in an unsupervised manner. In Drosophila, the association between odors and rewards is detected by DANs, whose activities promote synaptic plasticity from KCs to MBONs [17,38,39]. Additionally, a recent study reported that DANs are also activated by the innate value of each odor [40].…”
Section: Hebbian T-sne Induces Association Learning With Generalizationmentioning
confidence: 99%
“…The MBON representations are not formed entirely in an unsupervised manner. In Drosophila, the association between odors and rewards is detected by DANs, whose activities promote synaptic plasticity from KCs to MBONs [17,38,39]. Additionally, a recent study reported that DANs are also activated by the innate value of each odor [40].…”
Section: Hebbian T-sne Induces Association Learning With Generalizationmentioning
confidence: 99%